LELAYU : A SYMBOLIC REPRESENTATION OF FLOWER PORTRAITS - Permatasari, Agnes Indah; Rizki Akhmad Zaelani Harry; Muksin, Muksin (ISI Press Institut Seni Indonesia Surakarta, 2025)
Lelayu is a painting series consisting of six works. This art seeks to transcend stereotypes associated with beauty. In this instance, perception can ultimately establish a stereotype for evaluation, particularly in the realm of beauty, which often involves an exaggerated impression of imperfection—resulting in the designation of ugliness—within the framework of withering. The presence of beauty stereotypes motivates our work. The painting method, employing a symbolic representational approach, serves as a conduit to perception, both presuming that perception consists of sensory impressions that are invariably interpreted directly. Flowers serve as a defining symbol of beauty and are the subject matter of this work. The symbolic representation of flowers ultimately embodies beauty through the depiction of withered flowers. The flower is depicted as a subject on the canvas, creating a portrait format that evolves from the still life impression, serving as an evaluation of the stereotypical perception that arises between the appreciators and the artwork. The symbolism of solitary, wilting flowers in the landscape underscores the notion that beauty is not represented solely in perfection, but also in imperfection. The wilted flowers ultimately symbolize the news of death, rendering the journey towards wilting and death as a form of beauty.